Perbandingan Administrasi Negara Indonesia dan Korea Selatan dalam Mewujudkan Pemerintahan Efektif dan Akuntabel - Hesti Ramadani; Ziyan Arsiya Holilah; Shela Shela; Amirotun Nadia; Ade Fartini (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The term “comparison” in the context of Public Administration Science refers to an activity of aligning, analyzing, and identifying similarities and differences between various phenomena or objects under study. Meanwhile, administration is understood as a social phenomenon in which groups of people or citizens work together in an organized and purposeful manner to achieve certain collective goals.This research, entitled “A Comparative Study of Public Administration in Indonesia and South Korea in Achieving Effective and Accountable Governance,” aims to analyze both the similarities and differences between the two countries in terms of bureaucratic structure, public administration systems, and the effectiveness and accountability of governance. Indonesia and South Korea, as Asian nations with distinct historical backgrounds, governmental systems, and development trajectories, share a common vision of establishing a clean, transparent, and responsive system of governance.The study employs a qualitative descriptive approach using the literature review method, by examining various relevant academic and official sources. The main focus of the comparison lies in the bureaucratic and administrative systems of Indonesia and South Korea. The analysis also takes into account cultural characteristics and governmental structures, including the presidential system, legal framework, financial administration, and local government mechanisms.The findings of this research are expected to provide a comprehensive understanding of how differences in administrative structures and bureaucratic performance in both countries influence the effectiveness and accountability of their governments. Furthermore, the study aims to offer valuable insights for Indonesia in strengthening good governance and improving the quality of public service delivery.